Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 1557266854 species occurrences available in GBIF matching the query: { "Year" : [ "1000-2021" ] } The dataset includes 1557266854 records from 29619 constituent datasets: 16 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 24645 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 14 records from Discovered online: Hibiscus hareyae sp. nov. of sect. Lilibiscus (Malvaceae), threatened in coastal thicket at Lindi, Tanzania. 13 records from Planktic foraminifera abundance of Hole 19-185. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 4 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 14 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 312 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 6191 records from marine sediment metagenome Metagenome. 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 19 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 15 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 6 records from A Catalogue and Historical Study of the Odonata of Ecuador. 371 records from Bannwald Burghauser Forst. 1361 records from Códigos de barras de la vida en peces y zooplancton de México. 192 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 6 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 2 records from Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) - a new fossil diatom species from Lake Ohrid. 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 4 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 14 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 20 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 186 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 17 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 3003 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 393 records from Analysis of plasmidome of high-altitude lakes from the Andean Puna. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 5 records from Loricifera - SMF. 3 records from New records and their associated DNA barcodes of the butterfly family Hesperiidae in Tibet, China. 9 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 10517 records from Bryophyte specimens of The Nagoya University Museum. 32 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 29365 records from University of Guam Insect Collection. 833 records from Plant species from the sacred and community forests of Mono departement. 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 480819 records from KTP Ring Data. 44 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 298 records from Planktic foraminifera abundance of Hole 32-310. 584 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 19 records from Dinoflagellate abundance of Hole 81-554. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 4 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 8 records from Report on a collection of dragonflies (Odonata) from the Andaman Islands.. 10 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 2 records from Two new genera and species of Fidicinini Distant, 1905 with a re-description of Nosola Stål, 1866 (Hemiptera, Auchenorrhyncha, Cicadidae). 462 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 102 records from Nannofossil abundance of Hole 24-232. 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 23 records from Morphologische Daten von Natrix. 2 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 6 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 18 records from Collection botanique Lamy de la Chapelle E. (BOUM). 7552 records from Brown University Herbarium. 1056 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 90 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 19339 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 5282 records from MCP-Aves - Coleção de Aves. 2 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 52 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 46 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 135 records from Nannofossil abundance of Hole 36-329. 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 143 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 728 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 821 records from Bird specimens of Saitama Museum of Natural History. 382 records from orthopteracollections-nhmj-ioj. 2 records from Carnivores of Syria. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 5 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 11117 records from Collections of Bioclass, school #179, Moscow. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 301406 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 49 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 147 records from Range table from benthic foraminifers in ODP Hole 161-974B. 3 records from Notes on the taxonomy of some “ Astaena ” species described by Burmeister (Coleoptera: Scarabaeidae: Melolonthinae). 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 7 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 5 records from Contributions to the knowledge of Atlantic Canadian Histeridae (Coleoptera). 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 5 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 588 records from artsprosjektet_51-14_ophiostomatoid_fungi. 201 records from Biodiversity of springs and rock seepages 2003. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 10776 records from CEFS_16S_ITS. 1 records from The Indian net-casting spider name Deinopis goalparaensis Tikader & Malhotra is a nomen dubium (Araneae: Deinopidae). 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 11 records from Inventaire et regroupement de données Natura 2000. 1272 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 68 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 21 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 127 records from Planktic foraminifera abundance of Hole 37-332. 521 records from Schanzenanlage Bergham. 1 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 1 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 84 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 1157 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 22 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 833 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 6368 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 72 records from Total foraminifera counts of multinet POS231/3_MSN1332. 1120 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 160 records from AVJNF: Søholt Storskov, amphibian survey. 18 records from Naturtag. 20619 records from Herbier Louis-Marie (QFA) - Collection de lichens. 961 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 241 records from Amphibian Specimens of the Yamagata Prefectural Museum. 27 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 67 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 592425 records from Plant. 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 1 records from A taxonomic review of the genus Asterostegus (Echinodermata: Ophiuroidea), with the description of a new species. 4 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 108 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 22 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 395 records from Nannofossil abundance of Hole 37-334. 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 15 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 1089 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 59 records from Schulgelände SGD/Viersen. 2 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 1533 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 12684 records from Colecção Entomológica IIA. 1290 records from Flora genérica de las gramíneas del estado de Tlaxcala. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 1 records from Zur Kenntnis der Lithobiiden. 16995 records from MZFC/Coleccion de Aves. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 307 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): range chart in percentages of calcareous nannofossils. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 2 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 7339 records from Natural History Museum Maastricht (NL) - Herbarium. 7147 records from DMNS Egg Collection (Arctos). 8859 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 1300 records from Crustacean specimens of Bihoro Museum. 361 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 59 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 161 records from Total foraminifera counts of multinet SO117_MSN1244. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 5750 records from Vegetation Relevés of Main Vegetation Types of the Prioksko-Terrasnyi Biosphere Reserve (2020). 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 371 records from An updated checklist of aquatic plants of Myanmar and Thailand. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 22 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 1702 records from BioGIS - Bryophytes - HUJ collections. 6990 records from Ethnobotanical surveys species in Benin (West Africa). 87 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 5576 records from uncultured prokaryote Targeted loci environmental. 7 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 136 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 745 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 6387 records from Données naturalistes de Monsieur LAFAGE Denis. 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 759 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 7 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 51 records from Coccoliths in sediment core GIK23065-3. 2208 records from marine sediment metagenome Raw sequence reads. 1 records from Neotropical Monogenoidea. 60. Two new species of Gyrodactylus (Monogenoidea: Gyrodactylidae) from the armored-catfish, Pareiorhaphis parmula Pereira (Loricariidae) and from the cascarudo, Callichthys callichthys (Linnaeus) (Callichthyidae) from Brazil. 121 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 9 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 16 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 1 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 232 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 10 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 7 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 10 records from A review of Solierella Spinola, 1851 (Hymenoptera, Crabronidae) from Iran with description of four new species. 15 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 26159 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 17 records from Analyses of the recent components of sediment core PS1219-1. 3 records from The genus Aivalykus Nixon, 1938 (Hymenoptera: Braconidae: Doryctinae) with description of a new species from India and Arabian Peninsula. 62 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1482 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 3109 records from Insectes Hyménoptères Scollidés de France. 3621 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 2 records from Description of a new brachypterous scarab species, Orphnus brevialatus (Coleoptera: Scarabaeidae: Orphninae) from East Africa, with notes on flightlessness in the orphnines. 57 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 18 records from Revision of the Metallactus generosus species-group with a preliminary evaluation of the effectiveness of the endophallus morphology in distinguishing critical sibling species (Coleoptera: Chrysomelidae: Cryptocephalinae). 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 26 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 736 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 1 records from Redescription of larva of the South African endemic dobsonfly genus Chloroniella Esben-Petersen, 1924 (Megaloptera, Corydalidae), with a proposed terminology for Corydalidae larval sclerites. 916 records from IOW Natural History & Archaeological Society Marine Records. 15 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 15 records from Nannofossil abundance of Hole 10-93. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 6190 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 314 records from Base de datos de las especies maderables del género Dalbergia en México, registros del Herbario Nacional de México (MEXU). 25 records from Contribution to the knowledge of the genus Cordilura Fallén (Diptera, Scathophagidae) from Japan, with descriptions of three new species. 8 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 140 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 245 records from Planktic foraminifera counts of sediment core V14-77. 135 records from Waldi-Weiher. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 19 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 3 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 35 records from Données de NICOLAS Vincent (SAPROX). 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 6440 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 330 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 77 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 975644 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 9 records from Planktic foraminifera abundance of Hole 14-144. 413272 records from DATAVES. 2572 records from seawater metagenome Metagenome. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 530 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 3806 records from Heliconiine Butterfly Collection Records from University of Cambridge. 1 records from Redescription of Leptogyra bujnitzkii (Gorbunov, 1946) comb. nov., the first representative of the gastropod subclass Neomphaliones from the high Arctic. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 6 records from Planktic foraminifera abundance of Hole 53-418B. 122 records from Colección de Líquenes Austroamericanos Ex Herbario Regnelliano- FML. 16 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 1993 records from Berea College, Ralph L. Thompson Herbarium. 255 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 409 records from Distribution of nanoplankton at trap WR2. 38 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 79 records from Birdrace-Bielefinken-Bielefeld. 7443 records from Fish specimens of Toyama Science Museum. 121 records from Range table from ostracoda in ODP Hole 143-866B. 642 records from Análisis de la biodiversidad y servicios ecosistémicos para su aplicación en la toma de decisiones en el departamento de Boyacá/Boyacá Bio-Flora El Consuelo. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 1 records from First record of Cephenniitae in the Bismarck Archipelago, Papua New Guinea, with description of new species of Cephennodes and Cephennomicrus of Mussau and Manus Islands (Coleoptera, Staphylinidae, Scydmaeninae). 5999 records from Colección Limnológica Universidad de Antioquia. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 141813 records from Fermanagh Flora. 13251 records from Tachinid Recording Scheme - Tachinid fly records verified via iRecord. 4 records from Pheronema on the mid-Atlantic Ridge, data from NRCan. 178702 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 2 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 1111 records from Catopsilia butterfly specimens at Museum Zoologi Bogor, Indonesia. 78 records from Données de la naturaliste Anna Even. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 18 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 1 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 14576 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 4 records from Dinoflagellate abundance of Hole 14-144. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 8 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 90 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 18 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 10 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 2 records from A new species of Platyauchenia Stürm, 1843 (Coleoptera: Chrysomelidae: Cassidinae) from Brazil. 26604 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 191 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 4 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 10 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 95 records from Kystfuruskoger i Tysnes og Fusa. 134 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 79 records from Diatom abundance of Hole 95-613. 1943 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 78 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 28075 records from Lepidoptera specimen database of Japan. 5 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 23 records from Abundance of benthos infauna at station GIK23042-2. 68 records from Streuobstwiese. 37 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 273 records from Planktic foraminifera abundance of Hole 68-503B. 130 records from BIRDRACE - The famous Grouse feat. The James. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 247 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 42972 records from VIES herbarium - Universidade Federal do Espírito Santo - Herbário Virtual REFLORA. 2729301 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 3400 records from Butterflies of Singapore and Peninsular Malaysia (Nymphalidae). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 7718 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 390 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 4585 records from Marine bacteria Targeted Locus (Loci). 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 280 records from Atlantic Forestry Centre Insect Reference Collection. 2 records from Review of the species of Anastatus (Hymenoptera: Eupelmidae) known from China, with description of two new species with brachypterous females. 11873 records from Midden-Limburg Fish Ponds Survey. 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 2743 records from marine sediment metagenome Raw sequence reads. 96 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 78458 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 7 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 4 records from A new scale insect host family (Hemiptera: Asterolecaniidae) for Aphytis (Hymenoptera: Aphelinidae) in China. 794 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 895 records from Geometridae de France métropolitaine. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 1215 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 96 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 1469 records from Marine eukaryotes Targeted loci environmental. 181 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 150 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 9 records from The Amphibians of the Mitaraka massif, French Guiana. 12 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 168 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 2704 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 298 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 4 records from Descriptions of two new Vietomartyria species (Lepidoptera, Micropterigidae) from China. 15360 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 71862 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1199 records from Oxygen minimal zone Targeted loci environmental. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 1290 records from Diversity of Spiders from Azorean Trails. 4 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 13 records from Lane 6 Analysis. 10354 records from Inventaire de la flore de Charente-Maritime 2018. 3939 records from Census of plant species in Pahou forest reserve. 4 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 10719 records from Inventario de Hymenóptera; parasítica en México. 327 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 7388 records from Ibaraki Nature Museum, Fungi collection. 2 records from A new genus and species of anophthalmous Otiorhynchini from Greece, with a new synonymy and new combinations (Coleoptera: Curculionidae, Entiminae). 1785 records from 3Soil16S. 67 records from Relative abundance of ostracods in sediment core Sv09. 923 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 781 records from Ecological study of the plankton in the port of Ostend in 1965. 744 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 192 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 384 records from Saltern microbial community diversity. 93599 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 36 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 49 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 24 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 30 records from Nannofossil abundance of Hole 24-233A. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 24 records from Dinoflagellate abundance of Hole 28-274. 11 records from The types of skippers described by Shu-Iti Murayama (Lepidoptera: Hesperiidae). 20442 records from Trondheim urban biodyversity survey. 94 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 142 records from Size of planktic foraminifera at CTD station PS55/083-1. 303 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 34534 records from R. L. McGregor Herbarium Lichen Collection. 64 records from Bats of northeastern Vietnam. 1052 records from IBF Monitoring of Fungi. 261 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 96442 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 6 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 1184 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 6479 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 35 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 197 records from New and little-known sun-moth species from Australia (Lepidoptera, Castniidae). 23 records from Taxonomic Accounts With Notes On Spatial Diversity And Relative Abundance Pattern Of Horseflies (Diptera: Tabanidae) From Sonamukhi Protected Forest Area Of West Bengal, India. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 66 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 207 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 69 records from BIRDRACE Pfeifenten. 70 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 23449 records from Port Phillip Bay Environmental Study Data 1992-1996 - benthic records. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 7 records from A new crab-associated amphipod of the genus Isaeopsis Barnard, 1916 (Amphipoda Senticaudata: Ischyroceridae) from southern Chile. 147 records from Données de la naturaliste Laurence Beauchamp. 240 records from Knechtweide (Kohlfurth). 4981 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 92 records from Collections ichtyologiques et herpétologiques (BOUM). 1405 records from MCP-Mamiferos - Coleção de Mamíferos. 11 records from Benthic macrofauna abundance of sediment core 12930-073. 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15040 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 336 records from Stable isotope data and sedimentology of core SO42-74KL. 68 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 89 records from Meniscus Midges (Dixidae) of Ireland. 2 records from A new species of the genus Tagasta Bolivar, 1905 (Orthoptera: Pyrgomorphidae) from India. 20 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 286 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1744 records from Occurrence database of native plants and animals of south-central Chile. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 1 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 6186 records from NE Scotland fish records 1800-2010. 259 records from Natura 2000 Parc naturel régional de Lorraine. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 50 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 2 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 2 records from Hangzhou-sediment-sample Raw sequence reads. 261 records from bmhs_weatherheadshell_collection. 57919 records from Fichier communal des ongulés. 208 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 18 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 21 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 6 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 4335 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 42 records from Living Cirripedia. 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 2070 records from Helmintos parásitos de peces del sureste de México. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 473 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from A new pseudoscorpion genus from western Georgia (Pseudoscorpiones: Neobisiidae: Cornuroncus n. gen.), with a key to all Neobisiinae genera. 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 222 records from Land and freshwater molluscs of Northern Spain. 1831 records from The Belgica 121 expedition to the Western Antarctic Peninsula: a high resolution biodiversity census. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3753 records from Données naturalistes de Charlotte PICARD. 1 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 4 records from Ostracoda abundance of Hole 44-390. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 3 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 11216 records from University of Nebraska State Museum Birds Collection. 115 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 8 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 27349 records from University of California Santa Barbara Invertebrate Zoology Collection. 356 records from Données naturalistes de Hubert GUIMIER. 1807 records from Données de la collection Rousset -1947-2013. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 57 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 143 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 2 records from A new species of planthopper in the genus Myxia (Hemiptera: Auchenorrhyncha Cixiidae) from the Reserva Privada el Silencio de Los Angeles Cloud Forest in Costa Rica. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 90 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 6079 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 12094 records from Amino acid addition experiment Metagenome. 7 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 3131 records from Données DREAL Centre-Val de Loire - Faune - 2018. 140 records from Hartland Nature Club Lepidoptera Collection. 117165 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 26 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 114234 records from Fish specimens of Kagoshima University Museum. 48476 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 13662 records from UTEP Invertebrates (Arctos). 3777 records from Diptera Collection of Museum and Institute of Zoology PAS. 9 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 17 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 246077 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 14 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 11045 records from Oregon Bee Atlas Survey Data: 2018. 9 records from Hybrizontinae (Hymenoptera, Ichneumonidae), a new subfamily for the fauna of Turkey. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 104 records from Birds Specimens of Akita Prefectural Museum. 1070 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 3 records from Rideriana amazonica gen. nov. and sp. nov. of Pentatomini (Heteroptera, Pentatomidae). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 101 records from Données naturalistes de LE GLOANEC Vincent. 177831 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-78. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 185 records from Size of planktic foraminifera at CTD station PS55/051. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 557 records from Corn bunting breeding distribution in Scotland. 7122 records from Whale catches in the Southern Ocean. 1 records from -- First- - description -- of- - the- - male- - of- - Dendrothrips karnyi (Thysanoptera, -- Thripidae) - from- - Iran. 405 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 3228 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 71 records from Foraminifera species abundances from tow TT007_7-MOC13. 15 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 6 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 40793 records from Banded Iron Formation and Greenstone survey data. 230 records from Biometría peces Parque Nacional Natural La Paya. 38 records from Microzooplankton abundance and biomass at station TT045_19-3. 43 records from Hydroptilidae (Trichoptera) of Angola, a new genus, seven new species, and five new records. 4 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 82 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 95 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 5 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 5 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 3 records from Denitrification bacteria in sediment cores of Daya Bay, China. 25 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 5 records from Données naturalistes de Mikaël PAILLET. 4379 records from Wild Bee Specimens from Blueberry and Raspberry Farms in the Champlain Valley, Vermont, USA. 4607 records from Données de type contact en Guadeloupe. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 351728 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 1767 records from Canadian Museum of Nature Palynology Collection. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 655 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 8 records from Revision of Afrotropical species of the Philonthus peripateticus species group (Coleoptera: Staphylinidae: Philonthina). 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 4 records from A new, uniquely patterned spiny eel (Teleostei: Mastacembelidae) from southern Borneo, Kalimantan Tengah, Indonesia. 15 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 130 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 55 records from Galls on Beech Trees in Hainich, 2008. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 181825 records from Carnet B Lorraine. 31 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 26 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 360958 records from Seasearch Marine Surveys in England. 27 records from Planktic foraminifera abundance of Hole 84-566C. 640 records from Annales de la Société Linnéenne de Maine-et-Loire. 6 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 10 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 1722 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 9756 records from Collection Trichoptera - SMF. 11433 records from Insectes Hétéroptères Mirides de France. 12 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 8 records from Taxonomic notes on the tribe Dryptini Bonelli, 1810 with description of a new genus and species from China (Coleoptera: Carabidae: Dryptini). 561 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 618 records from Pollen analysis of sediment core GeoB6518-1. 99 records from Planktic foraminifera abundance of Hole 27-262. 1910 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 494248 records from BLS Mapping Scheme dataset, 1750-2009. 27 records from Planktic foraminifera abundance of Hole 27-260. 130052 records from Arizona State University Hasbrouck Insect Collection. 1114 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 1 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 236 records from Collection Strepsiptera SMF. 62 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 3353 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 50 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 26 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 24 records from Revision of the New World species of the genus Dinotrema (Hymenoptera: Braconidae: Alysiinae). 4000 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 29 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 10 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 620 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 275 records from Composición florística de áreas degradadas por actividad minera a cielo abierto en el municipio de Condoto-Chocó, como insumo para calcular la biomasa vegetal, 2017. 87901 records from MDFRC macroinvertebrate survey. 1 records from Planktic foraminifera abundance of Hole 54-420A. 128 records from Inventaire des reptiles 2014. 8 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 40135 records from DIBA-Parc del Montnegre i el Corredor. 4761 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 238466 records from University of Tartu Natural History Museum and Botanical Garden Zooloogical Collections. 58 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 28994 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 8 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 1993 records from Inventario de macroalgas de Isla Guadalupe, México. 144 records from Cepario de Microorganismos y Hongos Filamentosos de la Universidad del Valle. 7 records from Grundwasserlebensraum im Englischen Garten (München). 53 records from Description of lithologic section units of IODP Hole 325-M0043A. 208 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 12 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 3 records from Description of a new species of the Rhinolophus trifoliatus-group (Chiroptera: Rhinolophidae) from Southeast Asia. 830 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 8218 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 753 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 6695 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 2939 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología (Mexicanos). 42696 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 365 records from HBRG Invasive Non-native Plants Dataset. 253 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 11 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 3240 records from Inventario florístico de la Sierra de Huautla, Morelos. 120 records from BIRDRACE The early birds. 6 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 2132 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 186099 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 9 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 44 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 45 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 1 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 20839 records from Birds Specimens. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 94 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 6979 records from Upper Silesian Museum, Bird Observations. 53 records from Planktic foraminifera abundance of Hole 23-227. 145 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 9 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 20815 records from DMNS Mammal Collection (Arctos). 758 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 5 records from Morphological and molecular description of a new genus and species of black coral (Cnidaria: Anthozoa: Hexacorallia: Antipatharia: Antipathidae: Blastopathes) from Papua New Guinea. 269 records from SEWBReC Springtails and allies (South East Wales). 2 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 22 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 536 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 22 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 4617 records from Inventaire de la flore du Grand Poitiers 2009. 23 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 1513 records from M. Gollop Collection. 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from Données naturalistes d'Olivier DELZONS. 49118 records from Naturalis Biodiversity Center (NL) - Diptera. 37 records from FBIP: scallop population genetics. 95 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 18 records from Schulgarten der Gesamtschule Am Heidberg. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 22 records from New species of Condylostylus Bigot (Diptera: Dolichopodidae) from Comoros Madagascar, Tanzania and South Africa, with key to Afrotropical species. 1270 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 14 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 17 records from Plant-parasitic nematodes of Republic of Karelia. 8 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 137 records from Colección Ficológica del Herbario Criptogámico de la FML. 62 records from Données naturalistes de BONCHE Jérôme. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 2099 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 3012 records from Distribution of foraminifera of sediment core GIK23258-2. 352 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 81329 records from natagora-earlybirds. 9143 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 16 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 2465 records from Elaboration de table de tarif de cubage multispécifique (I). 13 records from Reptiles Specimens of Akita Prefectural Museum. 97 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 205 records from UWIZM Snakes. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 80 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 16 records from Insect Collections of Okomu National Park- Nigeria. 281625 records from ARABEL - Arachnologia Belgica. 124513 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 1 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 1 records from Rediscovered syntypes of Procrangonyx japonicus, with nomenclatural consideration of some crangonyctoidean subterranean amphipods (Crustacea: Amphipoda: Allocrangonyctidae, Niphargidae, Pseudocrangonyctidae). 182 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 141 records from Biodiversity survey of Rugezi wetland, Year 2013. 62791 records from MLZ Bird Collection (Arctos). 449 records from Artsprosjekt Pyrenomycetes. 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 75152 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 121 records from Etude écologique du Parc des Lilas (94). 10 records from Données bibliographiques ASFRA. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 5061 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 720 records from Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Description of the previously unknown sexes in four West African Lycaenidae (Lepidoptera) with new data on their distribution. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 61 records from Shrews of Poland. 40 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 1 records from A new African species of Stenichnodes (Coleoptera: Staphylinidae: Scydmaeninae). 9 records from Nannofossil abundance of Hole 2-11. 46755 records from Données naturalistes de Pascal Dupont. 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 18 records from suivi du site Natura 2000 Carrière Saint Nicolas. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 2170 records from Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 348 records from Bird specimens of Bihoro Museum. 310 records from Registros de macroinvertebrados acuáticos en un bosque seco del municipio de Honda. 4 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 147 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 15 records from Nannofossil abundance of Hole 6-48B. 2 records from Wie viel Natur gibt es im Park?. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 598 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras en 2019. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 29876 records from European Moth Nights. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 3 records from A new species of Bicoxidens Attems, 1928 (Diplopoda, Spirostreptida, Spirostreptidae) from northern Zimbabwe. 1096 records from Zootaxa. 6779 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from A review of South Korean Alloplasta Förster (Hymenoptera: Ichneumonidae: Banchinae) with description of a new species. 10150 records from NBMB Herps. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 128 records from Données espèces - Expertise IPE 10. 63 records from Marine gastropod distribution from patagonian shallow waters. 797 records from Mycological collection of the National Museum. 3 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 78 records from Herbarium BSG Hepaticopsida. 19 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 20 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 18 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 14 records from The genus Anacroneuria Klapálek, 1909 (Plecoptera: Perlidae) from Maranhão State, northeastern Brazil. 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 354 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 10269 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 10 records from Description Of Six New Species Of Spiders Of The Genera Lathys (Family: Dictynidae), Marpissa (Family: Salticidae), Misumenoides (Family: Thomisidae), Agroeca (Family: Clubionidae), Gnaphosa (Family: Gnaphosidae) And Flanona (Family: Lycosidae) - From India. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 110 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 71 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6433 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 16 records from Dinoflagellate cysts of surface sediments. 7 records from Collection Malakologie - SMNG. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 50 records from Données d'observation de phanérogames marines en Martinique. 1264 records from Grand Voyeux - Suivis scientifiques. 44 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 164 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 1 records from Rocky-intertidal cheilostome bryozoans from the vicinity of the Sesoko Biological Station, west-central Okinawa, Japan. 1721 records from Phytoplankton data collected from the Black Sea during November 1957 (Cruise 2). 77 records from UWIZM Cnidarians. 356 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 145 records from Nannofossil abundance of Hole 67-499. 374 records from Coastal and Marine Species Database. 272 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 900 records from Convention Fédération française de golf - MNHN 2016-2019.. 173843 records from Tasmanian Museum and Art Gallery provider for OZCAM. 962 records from TTRS Mammals. 3 records from A new species of Tambitnotia from Peru, with the first reported female of the genus (Lepidoptera: Tortricidae: Olethreutinae). 224 records from Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 32 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 11 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 15 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 579 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 2 records from Benthic foraminifera abundance of Hole 42-376. 1235 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 45 records from Brown bear monitoring data from Deosai National Park. 862 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 254 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 5897 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 242 records from UTEP Fish (Arctos). 1 records from Two new species of Leptarma (Decapoda, Brachyura, Sesarmidae) from the Western Indian Ocean with notes on their phylogeny. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 4 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 97797 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 138 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 2 records from Rediscovering Anhanga: redescription and considerations on its taxonomic placement (Hemiptera: Heteroptera: Pentatomidae). 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1636 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 1066 records from Territorial Andes Occidentales - Densidad poblacional VOC subsistema cámaras trampa, 2018. 2590 records from Bryozoa, Brachiopoda and Entoprocta from the collection of the Arctic University Museum of Norway in Tromsø. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 41 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 1 records from Aenigmaphes gen. n., a new glandulariine genus of the Australian region (Coleoptera: Staphylinidae: Scydmaeninae). 860 records from Registros biológicos asociados al monitoreo de la diversidad de escarabajos en paisajes ganaderos silvopastoriles - Unillanos 2019. 4306 records from Saproxylic and herbivorous beetle species in old near-natural and old managed forests in south-eastern Norway. 24 records from A review of the species of Anaspis (s. str.) similar to A. nigripes Brisout and A. apfelbecki Schilsky, with the description of three new species (Coleoptera: Scraptiidae). 1 records from A new species of freshwater Chaetonotidae (Gastrotricha, Chaetonotida) from Obodska Cave (Montenegro) based on morphological and molecular characters. 89 records from Faunal assemblage of sediment core TR149-32. 61 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 7 records from New species of Clavigeritae (Coleoptera: Staphylinidae: Pselaphinae) from Malawi and South Africa. 3766 records from Benthic foraminifera distribution of sediment core GIK17957-2. 1 records from A new genus and species of pigeon (Aves, Columbidae) from the Kingdom of Tonga, with an evaluation of hindlimb osteology of columbids from Oceania. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 2 records from Potamocloeon edentatum sp. n. from Usambara Mountains in Tanzania (Ephemeroptera, Baetidae). 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 2 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 224 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 165 records from Ten new species of Phyllodoce Lamarck, 1818 (Phyllodocidae, Annelida) from Brazil. 8 records from Hemibates koningsi spec. nov: a new deep-water cichlid (Teleostei: Cichlidae) from Lake Tanganyika. 370 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 159 records from Total foraminifera counts from multinet M31/3_MSN915. 925474 records from NatureServe Network Species Occurrence Data. 41676 records from Tagged Seal Location Data from SOGLOBEC. 3 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 333 records from Données naturalistes de Renaud PUISSAUVE. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 839 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 21 records from Contribution to the Asian and Afrotropical species of the genus Dyschiriodes (Coleoptera: Carabidae: Scaritinae). 1748 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 1709 records from The Gibson spider collection. 52 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 4 records from A new species of Scinax Wagler (Hylidae: Scinaxini) from the tropical forests of Northeastern Brazil. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 651 records from Réseaux écologiques/Trame verte et bleue. 460 records from (Fig. 1) Ice rafted debris and planktic foraminifers of Hole 94-609. 34 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 2 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 12 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 21 records from Herbarium Senckenbergianum (FR) - Protista. 243 records from Colección de helechos de la FML. 66164 records from Florida Keys Reef Visual Census 1996. 3 records from Zoology in the Middle East. 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 52646 records from Données de l'Observatoire de la Faune de Bourgogne. 848 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 2 records from Revision of the types of species of Alloxysta described by Cameron and Fergusson (Hymenoptera: Figitidae: Charipinae) and deposited in the Natural History Museum (London), including a key to the fauna of Great Britain. 13 records from Review of Scatimus Erichson (Coleoptera: Scarabaeidae) in Colombia with the description of a new species. 4147 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 228695 records from Wild bees of Belgium. 164 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 20 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 54 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 539 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 95 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 67 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 5559 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 288 records from Echinoderms from the Seaflower Biosphere Reserve. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 2 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 550 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 117 records from Nannofossil abundance of Hole 49-408. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 304 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 17 records from Analyses of the recent components of sediment core PS1011-1. 48 records from Total foraminifera counts of multinet M6/7_MSN140. 9143 records from Royal British Columbia Museum Entomology Collection. 62 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 33 records from Dinoflagellate abundance of Hole 81-552. 33 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 35 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 2110 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 5940 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 11 records from Eight new Lepadellidae (Rotifera, Monogononta) from the Congo bring to level endemism in Africa’s rotifers. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 6 records from Foraminifera abundance of Hole 58-442. 144 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 3001 records from Colección Entomológica CDMB. 1046 records from NZCS Invertebrates New Collection After 1987. 10122 records from Uncultured eukaryotes Targeted Locus (Loci). 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 16931 records from Lepidoptera (Specimens NRM). 13 records from Coleção de Coleoptera da Universidade de Brasília. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 98 records from Warnowtal (Rostock). 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 822 records from Las comunidades de myxomicetes de selva baja caducifolia. 49 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 489 records from Caracterización bionómica de zonas de dragado y de afección de obras en la Ría de Ferrol. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 27728 records from Collection of saproxylic and xylobiont Beetles. 2747 records from Compost microbe establishment and growth in agricultural soils. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 202122 records from National Benthic Inventory. 56 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 16 records from Phenological Center - Fishes (Murmansk). 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 358 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 22534 records from Tachinid Recording Scheme - GB and Ireland records. 111 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 1 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 2500 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 614 records from BID-Malawi-Geometridae-Biodiversity-Data. 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 164 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 111 records from Birdrace-Uhulogen-Lippe. 636 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 103 records from New taxa of the tribe Meconematini from South-Pacific and Indo-Malayan Regions (Orthoptera, Tettigoniidae, Meconematinae). 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 6901 records from La familia Asclepiadaceae en México. 22 records from Stable carbon and oxygen isotope record of Cretaceous planktonic foraminifera from DSDP (Table 1). 12 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 83 records from Birdrace-Die_Vogelscheuchen-Herford. 370 records from Otter survey of Ireland 2004 & 2005. 15277 records from JOI - Herbário Joinvillea. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 41 records from A revision of the African wolf spider genus Amblyothele Simon. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 6247 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 10 records from Four new species of the subgenus Pachylaelaps (Longipachylaelaps) from Italy, with a new identification key to the known species (Acari: Pachylaelapidae). 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 5 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 81 records from Birdrace-Die_Ornithomaten-Herford. 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 133152 records from Suivi Temporel des Rhopalocères de France (STERF). 29 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 1080 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 2 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 80649 records from NINA Vanndata fisk. 177 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 21 records from A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Galápagos Islands, Ecuador. 22 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 174 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 5 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 191 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 8006 records from Données naturalistes de Franck NOEL. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 820 records from Nannofossil abundance of Hole 82-558A. 2 records from A new Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the northern Western Ghats, Maharashtra, India. 365 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 3320 records from BioGIS - Mammals - SPNI. 2369 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 4 records from Revision of Sinonereis Wu & Sun, 1979 (Annelida: Nereididae). 160 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 1 records from A new species of freshwater crab of the genus Badistemon Yeo & Ng, 2007 (Decapoda: Brachyura: Potamidae: Potamiscinae) from Manipur State, India with the reassignment of Potamiscus pealianus (Wood-mason, 1871). 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 2 records from A new species of the subgenus Idopterum Hampson, 1894 of the genus Ammatho Walker, 1855 from China (Lepidoptera: Erebidae: Arctiinae: Lithosiini), with redefinition of the subgenus Idopterum. 118 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 130 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 13 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-104BX. 119365 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 150 records from Planktic foraminifera abundance of Hole 94-610B. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 754 records from Global database of alien macrofungi. 3417 records from MEXU/Flora de Oaxaca. 39654 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 2 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 2118 records from Registros biológicos de flora para el desarrollo de acciones de evaluación, seguimiento y monitoreo en los elementos priorizados de la estructura ecológica principal del distrito capital. Bogotá D.C.. 116 records from Arizona State University Lois B. O'Brien Collection. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 62 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 207 records from Nannofossil abundance of Hole 66-488. 2 records from Description of lithologic section units of IODP Hole 325-M0052C. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 8 records from Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic. 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 7326 records from Ravensthorpe Range survey data. 24 records from Scorpaena regina, a new scorpionfish (Teleostei: Scorpaenidae) from the east coast of Queensland, Australia. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 26897 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 49 records from Crickets of the subfamily Itarinae Shiraki, 1930 (Orthoptera: Gryllidae) from China with description of a new species and distribution and critical notes on other species. 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 5 records from Schulinnenhöfe (Gelsenkirchen). 1 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 2851 records from Données naturalistes d'Alain BERLY. 105925 records from Herps Specimens. 39092 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 6 records from New species of the leafhopper genera Sophonia and Stenotortor (Hemiptera: Cicadellidae: Evacanthinae) from the Oriental region. 12 records from Analyses of the recent components in the sand fraction of sediment core PS1012-1. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 31 records from Nanoplankton abundance at station GeoB2012-5. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 838 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 7490 records from Yoann_BLANCHON_2017_12_18. 60 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 250 records from Inventaire et regroupement de données Natura 2000. 2 records from Notes on the genus Gargela (Lepidoptera: Crambidae) ı with descriptions of two new species from China. 12724 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 231973 records from Données de la flore d’Alsace (SBA). 2 records from Pipunculidae (Diptera) from southern Iran, including two new species of the genus Tomosvaryella Aczél. 3 records from MSB Mammal Observations (Arctos). 5 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 10 records from Données naturalistes de Sophie COHEN. 696 records from the diversity of anammox bacteria in the subterranean estuary. 53 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 24880 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 13868 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 2 records from Description of Walkeriella miraculosa, gen. n. et sp. n. from South-East Peru (Lepidoptera: Hepialoidea: Hepialidae). 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 76 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 1 records from On the systematic status of Calliophis macclellandi nigriventer Wall, 1908 (Reptilia: Serpentes: Elapidae). 18 records from Anfibios presentes en el Cerro Jánano. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 26389 records from Protist Diversity in the East China Sea. 120 records from Données espèces - Expertise IPE 79. 1705882 records from NBIS Records to December 2016. 25 records from Planktic foraminifera abundance of Hole 51-417B. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 50 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 3 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 2590 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 20 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 728 records from South American Antarctic Marine Biodiversity Literature. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 5 records from A new species of Laccobius Erichson and additional faunistic records of the genus from China, with a key to subgenus Glyptolaccobius Gentili (Coleoptera: Hydrophilidae). 1 records from Recognition of a new species of Carmenta from New Mexico supported by morphology and mitochondrial cytochrome oxidase I data (Lepidoptera: Sesiidae: Sesiinae: Synanthedonini). 6 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 1900 records from Fungi Collection. 638 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 1 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 5 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 4107 records from California State University, Long Beach Birds. 87 records from Données espèces - Expertise IPE 70. 1028 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 18 records from Thirteen new records of ferns from Brazil. 575 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 130765 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 132 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 32694 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 152 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 26 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 90298 records from NE AVH data. 98 records from Description of lithologic section units of IODP Hole 325-M0033A. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 23 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 47 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 6279 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Données opportunistes sur les odonates. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 47 records from Schulgelände (Wetter). 282 records from Deponie Klausdorf. 31 records from The Brazilian Goblin Spiders Of The New Genus Predatoroonops (Araneae: Oonopidae). 5 records from First record and new species of the genus Calambus Thomson (Coleoptera Elateridae, Dendrometrinae) from Taiwan. 16844 records from Données Entomologiques A. HORELLOU 1988-2018. 1 records from A new species of planthopper in the genus Haplaxius (Hemiptera: Auchenorrhyncha: Fulgoroidea: Cixiidae) on palms in Costa Rica and a new country record for Haplaxius skarphion. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 30042 records from University of Jena, Herbarium Haussknecht - Herbarium JE. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 321 records from Foraminifera abundance of Hole 74-526A. 55 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1535 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1986 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 21 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 23 records from Benthic foraminifera abundance of Hole 42-379A. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 60 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 1489 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality – Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 903 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 2508 records from BioGIS - Reptiles - HUJ collections. 13 records from Analyses of the recent components of sediment core PS1222-1. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 232 records from Planktic foraminifera abundance of Hole 21-207. 652968 records from Flora Atlas N.T.. 8 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 24 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 82 records from Herbario COFC de la Universidad de Córdoba: colección histórica. 7 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 11174 records from WOLL AVH data. 2 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 2 records from Taxonomy of the Oriental leafhopper genus Parabolopona (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with a new species from China. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 84 records from Ostracoda abundance of Hole 48-403. 19 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 10 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 50 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 3638 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 24 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 8 records from A new species of Phonotimpus Gertsch & Davis, 1940 (Araneae: Phrurolithidae) from Mexico. 2718 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 129 records from Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 145 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 1856 records from Analysis of macrobenthos in the Southern Bight of the North Sea (1971-1972). 93 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 186 records from Interstitial and parasitic Platyhelminthes from the coast of the Seychelles in 1992 and 1993. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 10 records from Ostracoda abundance of Hole 32-306. 1 records from A new tyrannosaurine (Theropoda: Tyrannosauridae) from the Campanian Foremost Formation of Alberta, Canada, provides insight into the evolution and biogeography of tyrannosaurids. 27 records from The first species of Cotithene Voss (Coleoptera: Curculionidae: Curculioninae) from Amazonian Brazil, with notes on its role as a pollinator of Evodianthus funifer (Poit.) Lindm. (Cyclanthaceae). 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 526 records from Range table from benthic foraminifers in ODP Hole 151-913B. 198 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 146 records from Abundance of birds in the Lena Delta Region. 31 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 54 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 124 records from Kirkliston Range stream monitoring. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 1088 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 247 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 35 records from Ortsrand Zandershagen. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 31 records from Planktic foraminifera counts of sediment core V19-21. 67 records from artsprosjektet_48-13_monomyx. 1188 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 25138 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 5250 records from Colección Ornitológica de la Universidad del Valle. 7839 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 2763 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 21 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 338 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 32 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 162 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 1656 records from The ‘ red-tailed’ Lasioglossum (Dialictus) (Hymenoptera: Halictidae) of the western Nearctic. 188 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 214 records from Caracterización de vertebrados terrestres en el Cerro Guadalupe, municipio de Manzanares. 342 records from Foraminifera distribution of sediment core KS310. 1462 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 11131 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 2970 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 94 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 1036 records from BUND - Dassower See (Lübeck/Dassow). 59995 records from Données naturalistes de Monsieur François FOURNIER. 429 records from NHMO DNA Bank Other groups collection. 1 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 69 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 54298 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Sächsische Schweiz (Wehlener Gebiet). 4 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 23 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 15 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 42 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 22 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 3 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 16 records from El género Aleuroparadoxus Quaintance y Baker 1914, con descripción de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 522 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 587 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 4 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 3 records from Description of Bradinopyga konkanensis sp. nov. (Odonata: Anisoptera Libellulidae) from the coastal region of Maharashtra, India. 204499 records from University of Michigan Museum of Zoology, Division of Birds. 39 records from Planktic foraminifera abundance of Hole 14-137. 5 records from Meatopida gen. nov., a new genus to accommodate two species originally described in Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae). 2586 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 752 records from Données naturalistes de Monsieur JOURDE Rémi. 811 records from Données naturalistes de AUNEAU Florent. 2203 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 494 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 6 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 7 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 20 records from Taxonomic revision of the Afrotropical scarab beetle genus Cerhomalus Quedenfeldt, 1884 (Coleoptera: Scarabaeidae: Orphninae). 2 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 37 records from Collection Graptolithina fossil SMF. 10 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 25934 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 2 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 24 records from Suphisellus grossoi sp. n., a new burrowing water beetle from South America and notes on S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae). 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 3 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 130 records from Total foraminifera counts of multinet M21/6_MSN784. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 48 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 62 records from Zoo Frankfurt. 212 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 41 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 1085627 records from Fungal Records Database of Britain and Ireland. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 2 records from A new genus of Podoscirtini with one new species from Guangxi, China (Orthoptera: Gryllidae; Podoscirtinae). 31 records from Bulletin d'informations de l'Association française de Lichénologie. 38 records from Nannofossil abundance of Hole 10-89. 5 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 2 records from Two new species of Sinacroneuria Yang & Yang, 1995 (Plecoptera: Perlidae) from Guizhou, southwestern China. 91 records from Nannofossil abundance of Hole 30-285A. 144 records from A Revision of the Nearctic Predaceous Midges in the Bezzia (Bezzia) pulverea complex (Diptera: Ceratopogonidae). 752 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 61068 records from La familia Asteraceae en México. Fase VI. 356 records from Morphologische Daten von Puffinus creatopus. 505 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 23296 records from WTSWW Data: All Taxa (West Wales). 3 records from The spider wasp genus Telostholus Haupt, 1929 (Hymenoptera, Pompilidae) in Malaysia, with the description of four new species. 20020 records from Wikiplantbase #Sicilia. 123 records from NEON Biorepository Zooplankton Collection (Unsorted Bulk Sample). 384 records from Nannofossil abundance of Hole 17-167. 271 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 289 records from bmhs_butterfly_collection. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 498 records from Bekkelag basin, Inner Oslofjord. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 2023 records from Composición florística y estructura vegetal de una parcela permanente en un relicto de bosque seco tropical en el Caribe colombiano. 748 records from Phenological Center - Birds (Laplandskiy). 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 609 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 528 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 36 records from Benthic foraminifera abundance of Hole 42-380. 57 records from Inventaire faune flore de l'étang d'Abbecourt à Orgeval. 172 records from checklist-of-birds-of-zomba-mountain. 108775 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1142431 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 60 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 58 records from Composition of the smaller coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 1390869 records from Flore Franco-Belge. 62472 records from EAC - Herbário Prisco Bezerra. 91 records from CNIN/Tipos Homoptera. 29016 records from Marine Biological Sample Database, JAMSTEC. 1485 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 399 records from Otter (Lutra lutra), Outer Hebrides. 2 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1541 records from Leif Richardson Vermont Bee Specimens. 12 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 109 records from Planktic foraminifera abundance of Hole 18-181. 41 records from Calliostomatidae, Colloniidae, Margaritidae, and Solariellidae (Gastropoda: Trochoidea) collected by the Marion Dufresne (MD 55) expedition in southeastern Brazil, with description of a new species of Calliostoma. 2 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 4 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 165 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 20709 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 89 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 3 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 1 records from Solving a long-standing nomenclatorial controversy: designation of a neotype for the southern sea lion Otaria flavescens (Shaw, 1800). 22 records from Notes on slender species of the long-jawed spider genus Tetragnatha (Araneae Tetragnathidae) with description of three new species. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1528 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 322193 records from Florida Keys Reef Visual Census 2010. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 10 records from A revision of the genus Anadenosternum Athias-Henriot (Acari: Mesostigmata: Parasitidae). 153 records from annex1. 123 records from Total foraminifera counts of multinet POS247/2_MSN1377. 53 records from Jumping plant-lice (Hemiptera: Psylloidea) of Afghanistan. 28 records from Dinoflagellate abundance of Hole 28-270. 693 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils at DSDP Hole 93-603B. 4 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 106 records from Rare vascular plant species in North-West of Kostroma region, Russia. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 63 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 52 records from FBIP: Establishment of a fully data-based and barcoded collection of mushroom pathogens for South Africa. 2 records from Microfossil abundance of Hole 21-208. 1680 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 150 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 114 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 2041 records from marine metagenome Targeted Locus (Loci). 333 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 8197 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_Palearctic. 26635 records from Plan de vertebrados de la Patagonia. 1 records from Notes on the genus Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from India with description of a new species. 9 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 61 records from Planktic foraminifera distribution of sediment core TRI171-27. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 6 records from Four new species of the genus Pseudosubhimalus (Hemiptera: Cicadellidae) from the Indian subcontinent. 332 records from Swedish Malaise Trap Project (SMTP) - Sepsidae. 22 records from Description of lithologic section units of IODP Hole 325-M0054B. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 2852 records from AlgaTerra. 735 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 174 records from Planktic foraminifera abundance of Hole 22-217. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 1 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 820 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 13000 records from LPO_PACA_2017_12_18. 8 records from Nannofossil abundance of Hole 39-353A. 47 records from Abundance and community structure of birds breeding in Kalahari woodland used as rangeland. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 38 records from The Elachistidae (Lepidoptera: Gelechioidea) of Caucasus, with description of three new species. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 7114 records from HSU Vertebrate Museum Mammals Collection. 40 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 13 records from Nannofossil abundance of Hole 9-80. 9 records from Umbyquyra gen. nov., a new tarantula spider genus from the Neotropical region (Araneae, Mygalomorphae, Theraphosidae), with a description of eight new species. 37445 records from ADDOMEx. 10825 records from Census of species recorded during phytosociological surveys in Benin. 1 records from The InBIO Barcoding Initiative Database: Wesmaelius (Kimninsia) nervosus (Neuroptera, Hemerobiidae): a new species of brown lacewing for the Portuguese fauna. 305 records from Foraminifera abundance of Hole 57-440B. 117 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 238 records from List of Macroinvertebrate Species recorded in Vava’u during BioRAP survey. 6664 records from Coral or reef-seawater associated bacteria Targeted Locus (Loci). 6468 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 1 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 244 records from Informatisation des carnets de terrain de Georges Catherine. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 4 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 98734 records from Acoustic monitoring data of avian species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 4 records from The genus Pseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae: Eumeninae) in the Philippine Islands, with description of a new species. 27226 records from UTEP Insects (Arctos). 5364 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 27 records from A new genus and two new species in the tribe Selizini (Hemiptera: Fulgoromorpha: Flatidae) with a checklist for the tribe from China. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 7 records from Revision of the Genus Schizoretepora (Bryozoa, Cheilostomatida) from the Atlantic-Mediterranean region. 10 records from Données naturalistes de DURON Cyril. 19571 records from Collection Pisces SMF. 1169 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 2 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 244 records from Nannofossil abundance of Hole 29-281. 26 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 2 records from Morphological and molecular evidence of a new species of Melanochlamys (Gastropoda: Heterobranchia) from the Bohai Sea, China. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 580 records from Rare plants database extract from Scottish Natural Heritage. 11 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 194 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 2497 records from Données des collections d'algues du MNHN. 16094 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 302 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 1 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 68377 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 422150 records from NOAA AFSC North Pacific Groundfish Observer. 27160 records from Formidabel; Belgian Ants Database. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 32 records from Revision of the genus Neozavrelia Goetghebuer, Thienemann, 1941 (Diptera Chironomidae) from Eastern Siberia and the Russian Far East, with the description of new species. 1148 records from ABC event data for Nyika Plateau, Buma Hills. 64 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 16 records from Hazel Dormouse in Ireland. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 100 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 3 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 16 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 115 records from Total foraminifera counts of multinet M21/4_MSN694. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 2352 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 119 records from Suivi des leucorrines sur le site du Marais du Plata. 46435 records from ALCB herbarium - Universidade Federal da Bahia - Herbário Virtual REFLORA. 37 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 46 records from An der Ohm, (Wettsaasen). 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 29986 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Vascular Flora and Habitats: species of conservation concern (RELAPE) - [2010-2014]. 568 records from Philippine Mollusk Symbiont - ICBG Collection. 185 records from Inventaire des odonates d'intérêt communautaire. 1270 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 168 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 127 records from Сypripedium guttatum Sw. in the Komi republic. 2116 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 2418 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 11 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 510 records from Inventaires des cygnes du département de l'Eure. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 41 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 364 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 25 records from Herpetofauna de la expedición Piedemonte Llanero - Proyecto Boyacá BIO UPTC. 96 records from Peces de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 361 records from Données de VINCENT Alexis (SAPROX). 53062 records from British Antarctic Survey Argos satellite tracking data. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 39 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 56 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 230880 records from Soil bacterial diversity is associated with human population density in urban greenspaces. 3 records from Distribution of meiobenthos in sediment core M19_217-2 of the northeastern Atlantic (Table 1). 113 records from Total foraminifera counts of multinet M26/1_MSN844. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 51 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 361 records from Nannofossil abundance of Hole 66-490. 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 3 records from Nesting biology of Paragymnomerus signaticollis tauricus (Kostylev, 1940) (Hymenoptera: Vespidae: Eumeninae). 2679 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 5856 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 1 records from On some species of the genus Acrolocha Thomson, 1858 of the Western Palaearctic Region (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 584 records from Données du naturaliste Christian Desmier. 10 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 330 records from Fossil Specimens of Komatsu City Museum. 478 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 836 records from Odoanta of Akwa Ibom State University, Nigeria. 1134 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 2691 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 41141 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 23130 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 120716 records from Microbial biogeography of 925 geothermal springs in New Zealand. 39 records from Inventaire Faune. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 59 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 208 records from Registros de arañas en el marco del proyecto Influencia de la dieta sobre la toxinología y toxicología en arañas. 36 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 4 records from Revision of the genus Carybdea (Cnidaria: Cubozoa: Carybdeidae): clarifying the identity of its type species Carybdea marsupialis. 30 records from The larva of Amphigomphus somnuki Hämäläinen, 1996 and the first records of the genus Stylogomphus Fraser, 1922 for Thailand (Odonata: Gomphidae). 133 records from Planktic foraminifera abundance of Hole 42-375. 70 records from (Fig. 5) Distribution and stable isotope record of foraminifera, and ice-rafted debris of sediment core PS1230-1 (fig 5). 15 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 17827 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 242 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 31 records from Planktic foraminifera abundance of Hole 32-305. 6 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-960A. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 14426 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 51 records from Total foraminifera counts from M35/1_MSN1051. 1514 records from Gemeinde Sursee. 6 records from Review of the genus Shilovia Makarchenko (Diptera: Chironomidae: Diamesinae Boreoheptagyiini) from the mountains of Central Asia, with morphological description and DNA barcoding of known species. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 3 records from Sponges of the family Esperiopsidae (Demospongiae, Poecilosclerida) from Northwest Africa, with the descriptions of four new species. 74 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 525 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 183 records from Nannofossil abundance of Hole 67-496. 852 records from Observatoire des Mammifères marins de l'Archipel Guadeloupéen. Suivi Dauphins Les Saintes. 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 1863 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 1375 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 1 records from On Megalepthyphantes lydiae Wunderlich, 1994 (Araneae: Linyphiidae). 465 records from Hyperbenthos community in the salt marsh of Saeftinghe in 1990 and 1991. 16 records from jamaica_invasive_alien_species. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 49 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 54 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 3 records from A new species of the spider genus Phlogiellus (Araneae, Theraphosidae) from Hainan, China. 1 records from A new tardigrade species of the genus Neostygarctus Grimaldi de Zio et al., 1982 (Tardigrada, Arthrotardigrada) from the Great Meteor Seamount, Northeast Atlantic. 7735 records from Odonata de Veracruz. 85 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 2 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 612 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 150 records from Schulgarten Huttenheim (Philippsburg/Baden). 436 records from Chinese species of Pediobius Walker (Hymenoptera: Eulophidae). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 1319 records from Inventaire et suivi Avifaune. 79 records from Planktic foraminifera abundance of Hole 63-470A. 7627 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 817 records from The Masao Oita Insect Collection of The University Museum, The University of Tokyo. 43 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2247-1. 6 records from A new species of Notacanthurus Tshernova, 1974 (Ephemeroptera: Heptageniidae) from India. 2 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 9 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 7 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 59 records from Búsqueda de poblaciones de la liebre endémica Lepus flavigularis. 1593 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Wolf, (Canis lupus) Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) [camera-trapping] - [2011-2014]. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 4 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 248 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10305 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 286 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 35 records from New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ‘ Bush Blitz’ surveys of national reserves. 62 records from NEON Invertebrate Voucher Collection at Arizona State University. 626 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 16505 records from Database for alien invasive plants occurrences in Germany. 62 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 138 records from Gandaca butterfly specimens at Museum Zoologi Bogor, Indonesia. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 8969 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 9 records from A new Dicranophragma (Diptera: Limoniidae) from a hypogeous environment in Catalonia (Iberian Peninsula). 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 15 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 407 records from Strathclyde badger sett surveys 1996-2000. 80 records from Foraminifera distribution of sediment core SDSE189. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 169 records from The ceratioid anglerfishes (Lophiiformes: Ceratioidei) of New Zealand. 24097 records from OUPR - Herbário "Professor José Badini". 2017 records from Flore des reliques forestières de la commune de Dangbo. 10 records from Nannofossil abundance of Hole 58-442B. 5 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 4 records from Gynacantha vargasi (Odonata: Anisoptera: Aeshnidae) sp. nov. from Costa Rica. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 100 records from Registros de Palma de cera palma (Ceroxylon quindiuense) por medio de fotografías aéreas en el parque Chingaza. 338 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 2 records from A new species of the genus Foenatopus Smith (Hymenoptera: Stephanoidea Stephanidae) from India. 12385 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 15 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 21 records from Planktic foraminifera abundance of Hole 18-174. 74 records from Chronicle of Nature - Phenology of Mushrooms of Baikalsky State Nature Biosphere Reserve. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 11853 records from California State University, Long Beach Mammals. 226 records from Royal Saskatchewan Museum - Ichthyology Collection. 254 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 240 records from Tejidos de individuos colectados en el plan de monitoreo de biodiversidad en el bloque platanillo de la empresa Amerisur y en los bloques Rumiyaco, Venados y Burdyne de la empresa Gran Tierra, Putumayo. 981 records from Monitoreo de la ocupación del Oso Andino (Tremarctos ornatus) en el Parque Nacional Natural Chingaza. 5069 records from Données mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 2. 92 records from Nottekanal, Klasse 7 - 10. 45 records from Taxonomic review of the moth family Thyatiridae (Lepidoptera) from Yunnan province, China. 414 records from Percentages of planktonic foraminifera species in sediment core V30-40. 83 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 810 records from Environmental long read amplicons of soil fungi across Podzol soil profile. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 130 records from A revision of the Australian species of the genus Melobasis Laporte & Gory 1837 (Coleoptera: Buprestidae), Part 2 (Revision of the nervosa species group). 2863 records from Inventaire des Mollusques Sphaeriidae de France. 17073 records from données aranéologiques de CORNIC Jean-François. 23 records from Four new and three newly recorded species of Diduga Moore, [1887] (Lepidoptera Erebidae, Arctiinae) from China. 359 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 44 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 7048 records from Collection Crustacea - ZMB. 874 records from The Living Murray Fish data. 645 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 9 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 4429 records from "Categorization of the wild food plants and their importance for primate development in the natural forest of Akpe (Lama) in southern Benin.". 25 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 25974 records from Long-term Bird Census in Cigu 2004-2017. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 10 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 7 records from Contribution to the AIrotropical Ɨchneumoninae (Hymenoptera, Ɨchneumonidae) Irom Gabon and Sierra Leone, with descriptions oI Iive new species and two new subspecies. 2 records from Range table from planktonic foraminifers in ODP Hole 159-960A. 240 records from BARTH-Environnement_2017_12_18. 459 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 8 records from The green lacewing genus Austrochrysa Esben-Petersen, 1928 (Neuroptera: Chrysopidae) from China, with description of two new species. 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 493 records from Study of epibenthos and demersal fish in and around the thiocarbamate discharge area of the Belgian Continental Shelf (1977-1981). 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 156 records from Total foraminifera counts of multinet M21/2_MSN658. 10 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 5 records from Phytoseiid mites of Slovenia (Acari: Mesostigmata): new records and first description of the male ofAmblyseius microorientalis. 30 records from Nannofossil abundance of Hole 9-82. 34 records from Microzooplankton abundance and biomass at station TT043_11-1. 2660 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 37 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 1948 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 74 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 1784 records from Ghent university - Zoology Museum - Nematod Collection. 79 records from Swedish Malaise Trap Project (SMTP) - Syrphidae. 101 records from BIRDRACE Enger am Spektiv. 32 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 125 records from Total foraminifera counts from multinet M32/3_MSN956. 17 records from A stonefly species extinct in Europe (Taeniopteryx araneoides Klapalek, 1902, Taeniopterygidae, Plecoptera) is thriving in the Irtysh River in West Siberia and North Kazakhstan. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 66 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 6164 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 10 records from Données naturalistes de CLERGET sylvie. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 2 records from A new genus and species of grasshopper from China (Orthoptera: Acrididae Catantopinae). 13 records from Warnowufer Groß Klein. 7 records from Stadtrandlandschaft Apolda-Nord. 3 records from A new species of the genus Sovia Evans, 1949 from South Central Yunnan, China (Lepidoptera, Hesperiidae). 4 records from Systematics and convergent evolution in three Australian genera of Pepsinae spider wasps (Hymenoptera: Pompilidae). 3687 records from Clare Biological Records Centre Dataset 2004-2007. 2424 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 7 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 7 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 4 records from A new glass sponge genus (Hexactinellida: Euplectellidae) from abyssal depth of the Yap Trench, northwestern Pacific Ocean. 4080 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 15 records from Two new species of the genus Crangonyx Bate, 1859 (Amphipoda: Crangonyctidae) from the St. Marks River Basin with notes on the “ Crangonyx floridanus complex ”. 2 records from A contribution to the revision of Adorodocia Brenske (Coleoptera: Scarabaeidae: Rutelinae: Adoretini): a new peculiar species from Ankaratra, Madagascar. 17 records from The genera Agelosus Sharp, 1889 and Apecholinus Bernhauer, 1933 in Taiwan (Coleoptera: Staphylinidae: Staphylinini: Staphylinina). 174 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geográfico y el nicho ecológico en los procesos de divergencia evolutiva.. 50 records from Flora und Fauna im Brexbachtal. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 126 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 5248 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 3 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 244 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 717 records from Biological Collection, National Institute of Oceanography, Goa, India. 72170 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 133 records from Pollen profile II/B at Krumbach, Germany. 1579 records from Occurrence data set for wild food plant species in Zimbabwe's biodiversity hotspots. 961 records from ABC_Useful Plants of Malawi: Species used as Herbal aphrodisiacs. 19006 records from Weevil and Bark Beetle records via iRecord. 826 records from Insect specimens of Natural History Museum, Kishiwada City. 136 records from A revision of the genus Mesoconius Enderlein (Diptera, Micropezidae, Taeniapterinae). 18 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 16 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 1 records from V ° Contributo alla conoscenza dei miriapodi cavernicoli italiani. 3460 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 213 records from The Avian Collection of the Tana River Basin at the National Museums of Kenya's Ornithology Section.. 3 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 17 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 5621 records from Plan d'Aménagement participative de la Forêt Classée d'Alédjo (Togo). 1648 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 4 records from A new species of the Neotropical genus Beebeomyia (Diptera: Richardiidae) with observations of its biology on Dieffenbachia oerstedii (Araceae). 7 records from A review of the Barsine perpallida-B. yuennanensis species-group, with descriptions of six new species (Lepidoptera: Erebidae: Arctiinae). 11 records from Benthic macrofauna abundance of sediment core 13078-013. 1084 records from Planktic foraminifera counts of sediment core RC14-35. 263 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 5 records from A new species of Aoruroides Travassos & Kloss, 1958 (Nematoda: Oxyuridomorpha Thelastomatidae) parasite of the wood-burrowing cockroach Panesthia angustipennis spadica (Shiraki, 1906) (Blattodea: Blaberidae: Panesthiinae) from Japan with comments on the validity of the genus Aoruroides. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 30 records from Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species. 1296 records from Avifauna de los Parques Ecológicos Distritales de Montaña del Distrito Capital. 2 records from A new species of Aphantolana Moore & Brusca, 2003 (Crustacea: Isopoda Cirolanidae) from the Andaman Islands, northern Indian Ocean. 1569 records from Pollen record of sediment core Bokanjacko Blato 1. 25 records from New species and record of Nazeris Fauvel in southern China (Coleoptera, Staphylinidae, Paederinae). 661 records from Données espèces Expertise IQE 311. 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 27 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 2 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 4 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 6 records from A new species of Catomus Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from the Aeolian archipelago (Sicily, Italy). 61 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 61 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 2 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 53 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 1 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 993 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 111684 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 2 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 401 records from Planktic foraminifera distribution of sediment core SU81-07. 1632 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 466 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 86676 records from Marine Offshore Seabed Survey data held by JNCC. 12 records from Benthic foraminifera abundance of Hole 96-620. 99 records from Nanoplankton abundance at station GeoB2006-4. 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 316 records from Données naturalistes de Monsieur LEFEBVRE François. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 449791 records from Herbarium of Taiwan Forestry Research Institute. 25 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 23 records from Ackerrain Plönhagen. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1004 records from Données odonates. 243 records from Malawi-Histeridae-Biodiversity-Data. 426 records from Planktic foraminifera abundance of Hole 7-64. 29 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 85 records from (Fig. 4) Nannofossil abundance of Cretaceous profile Pré-Guittard, SE France. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 200716 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 214 records from Total foraminifera counts of multinet M21/1_MSN608. 5520 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 4644 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4046 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 272 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 78 records from Banco de Semillas de Boyacá. 2225 records from Données naturalistes d'Anaïs MAS. 2430 records from Microbial community diversity in Arctic marine sediments and Planktonic microbial. 862 records from Palynological analysis of sediment core GeoB9508-5. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 12 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 8144 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 65 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Abundance of benthos infauna at station GIK23065-1. 1205 records from uncultured eukaryote Raw sequence reads. 22661 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 33 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 3 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 10 records from Taxonomic noteson thegenusPseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae Eumeninae) from Vietnam with key to all known species in the Oriental region. 368 records from Colección de Crustáceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 2045 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 235 records from Pollen and spore abundance of Hole 42-381. 285139 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 8 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 13 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 46693 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1599 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 5 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 16767 records from NCSM Mammalogy Collection. 798 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 16 records from Nannofossil abundance of Hole 52-418. 90 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 84 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 11 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 235 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 1 records from Predatory Dinosaurs of the World. 4 records from A new brachypterous species of Phoberus MacLeay (Coleoptera: Trogidae) and status changes of species in the East African P. nigrociliatus group. 6 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 3317 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 8 records from The cavernicolous Oniscidea (Crustacea: Isopoda) of Portugal. 171 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 7 records from Swedish Malaise Trap Project (SMTP) - Mymar. 797 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 452 records from Nannofossil abundance of Hole 64-476. 35 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 16623 records from Colección general del plantas vasculares del Herbario JBB. 95889 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 216890 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 92 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 1569 records from Cowan Tetrapod Collection - Herpetology. 147 records from Total foraminifera counts from multinet M31/3_MSN898. 10 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 186 records from Phytoplankton abundance at station CD46_0705C#4. 600 records from Upper Silesian Museum, Bird Collection. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 48650 records from Royal Belgian Institute of Natural Sciences Mammal collection. 5 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 29 records from Hemmerder Schelk (Unna). 11 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 30998 records from Elephant Seal Sightings, Macquarie Island. 1003 records from A monograph of the genus Maladera Mulsant & Rey, 1871 of China (Coleoptera: Scarabaeidae: Melolonthinae: Sericini). 2 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 152 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 3 records from Description of a new species of Music frogs (Anura, Ranidae, Nidirana) from Mt Dayao, southern China. 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 5 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 4 records from Planktic foraminifera abundance of Hole 17-166. 283 records from Flux data of NU2_trap (Table A1). 10 records from Revision of the bee genus Chlerogella (Hymenoptera, Halictidae), Part I: Central American species. 2844793 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 228 records from Bishop's University Insect Collection (BUIC). 18 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 7 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 5346 records from Sediment metagenome. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15255 records from Anymals+plants - Citizen Science Data. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 71095 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1689 records from CNAN/Scorpiones. 94 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 2 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 5 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 400 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 4 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 19665 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba. 3 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 2193 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 243 records from Thistles species and abundance. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 10138 records from The Vascular Plants Collection of the University of Goettingen. 117 records from Nannofossil abundance of Hole 41-366A. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 3 records from А new species of Alona Baird, 1843 (Cladocera: Chydoridae) from the ancient Lake Ohrid. 34 records from Bohemannia auriciliella (Nepticulidae) specimen data. 29 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 74 records from Nannofossil abundance of Hole 39-359. 22 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 28 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 217 records from Inventaire des odonates 2014. 113 records from Nannofossil abundance of Hole 49-412. 16 records from Genética de la Conservación del Oso Andino en el Parque Nacional Natural Cordillera de los Picachos y área de amortiguación. 24 records from Abundance of benthos infauna at station PS1240-1. 1716 records from Marine algal flora of Flores and Corvo Islands, Azores. 5 records from New records of biting midges (Diptera: Ceratopogonidae) from the United Arab Emirates, with a description of a new species. 5 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 110 records from Données du Râle gris sur le territoire de la Guadeloupe. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 25 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 1054 records from Amphibian specimens of Kanagawa Prefectural Museum of Natural History. 694 records from données arachnologiques de CARR David. 19 records from Fishes from the Auckland and Campbell Islands, Cape Expedition, 1942-1944. 4 records from Nannofossil abundance of Hole 3-22. 3 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 6 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 1170 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 5 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 17 records from Review of Chinese species of the Oxylipeurus - complex (Phthiraptera: Philopteridae), with descriptions of two new genera and five new species. 57504 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 134 records from BIRDRACE Griffin Wood Warblers. 156 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 1 records from Porifera ZMK. 2 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 9 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 2143 records from Range table from benthic foraminifers in ODP Hole 154-929A. 112 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 46 records from Revision of the genus Tmesiphorus LeConte, 1849 (Coleoptera: Staphylinidae: Pselaphinae) from Japan. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 25985 records from JCT AVH data. 33 records from Planktic foraminifera counts of sediment core V28-128. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 21703 records from Heterogeneity of methane seep microbiomes in the NE Pacific. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 237 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 2 records from Bioacoustics review of Anatolian species of the predatory bush-cricket genus Saga (Orthoptera: Tettigoniidae: Saginae) with the description of a new species. 23 records from Exceptional diversity o
Keywords: GBIF; biodiversity; species occurrences